High data retrieval rates with SwissPedData for paediatric traumatic brain injuries in children’s hospitals: a multicentre, point-prevalence study (Swiss Medical Weekly, 2025)
STUDY AIMS: SwissPedNet aims to improve the quality of multicentre research through standardised documentation of routine healthcare data. Therefore, SwissPedData was developed as a set of defined common data elements to be documented in each electronic patient file in a standardised format. This study evaluates the preparedness of the ten SwissPedNet hospitals for SwissPedData before its nationwide implementation, focusing on: (a) whether the defined common data elements are effectively documented and can be retrieved for children presenting with traumatic brain injuries to paediatric emergency departments, and (b) analysis of the content of these common data elements to assess how children with traumatic brain injuries are treated in paediatric emergency departments across Switzerland.METHODS: This multicentre point-prevalence study, conducted in June 2023, included all children up to 16 years presenting with traumatic brain injuries to ten SwissPedNet paediatric emergency departments over one calendar week. To assess the documentation of common data elements, a questionnaire was developed, consisting of 21 common data elements defined by SwissPedData, covering patient demographics, accident details, symptoms, paediatric emergency department course, and if applicable, inpatient course. Each hub retrospectively collected data from the electronic health records of all traumatic brain injury patients during the specified week. The primary objective was to assess the rate of successful data retrieval, defined as the presence of documented information for specific common data elements. Data were classified as missing if no information regarding a specific common data element was found in the electronic health record. The retrieval rate of each common data element was evaluated, and the average time investment per patient was recorded to estimate the associated workload. The secondary objectives focused on the content of the compiled common data element information, assessing causes and symptoms of traumatic brain injuries and injury severity and comparing management procedures for traumatic brain injury patients across Switzerland. Logistic regression was used to assess associations between specific patient characteristics (e.g. symptoms), the probability of having computed tomography (CT) scans in paediatric emergency departments, and the rate of hospitalisations.RESULTS: During the study period, a total of 349 children with traumatic brain injury were treated; the median age was 4.0 years (interquartile range [IQR] 2.0–7.5 years). Data retrieval rates exceeded 90% for each common data element; specifically, common data elements with numeric information were extracted in 98.3% to 100% of cases, while those with standardised options or free-text entries had a retrieval rate of 91.7% to 100%. However, data on written discharge information were available for only 51.2% of outpatients and 53.3% of inpatients, with significant variability among hospitals. Data collection efforts varied among the ten participating hubs, with an average time investment per patient ranging from 0.5 to 2 hours and limited involvement of information technology (IT) departments. The prevalence of traumatic brain injury patients at the paediatric emergency departments was 6% (range: 3% to 11.5%), with most traumatic brain injuries occurring at home (48%) or on playgrounds (18.9%). The primary trauma mechanism was a fall (56.5%), usually from a height of less than 1 metre. Most patients (99.1%) had a normal Glasgow Coma Scale (GCS). CT scans were performed in ten cases in the paediatric emergency departments, revealing pathologies in four cases, and resulting in neurosurgical intervention in one case. Factors associated with undergoing a CT scan or being hospitalised included lower triage category numbers and loss of consciousness.CONCLUSIONS: Common data elements are conscientiously documented within clinical information systems for patients with traumatic brain injuries in paediatric emergency departments, but data extraction requires considerable time and effort, underscoring the need for additional technical support. Although traumatic brain injuries are a common reason for paediatric emergency department visits, they are generally mild in severity. Although Switzerland has no national guidelines for treating children with traumatic brain injuries, management practices, particularly the low rate of CT scans in children with traumatic brain injury and normal GCS, appear to be fairly consistent across hospitals.